Answer:
11th term is 0
Step-by-step explanation:
30, 27 , 24 ,......0
a = first term = 30
Common difference = second term - first term = 27 - 30 = -3
nth term = a+(n-1)*d
a + (n-1)d = 0
30 + (n - 1) *(-3) = 0
30 + n*(-3) -1*(-3) = 0
30 - 3n + 3 = 0
-3n + 33 = 0
-3n = -33
n = -33/-3
n = 11
Answer: x=
1
Step-by-step explanation: solve for x by simplifying both sides of the equation, then isolating the variable.
You have to multiply your 20cm by 6cm and your final answer being 120 because 0 times 6 is zero and 2 times 6 is 12, then that getting you 120
Answer:
12a³+2a²+23a+18
Step-by-step explanation:
(3a+2)(4a²-2a+9)=
12a³-6a²+27a+8a²-4a+18=
12a³+2a²+23a+18
If you need more explanation, reply to this answer.